The gene of a GPI-anchoring protein a promising new target for the control of the cucurbit powdery mildew Podosphaera xanthii. - Padilla-Roji, Isabel; Fernández-Ortuño, Dolores; Pérez-García, Alejandro (My University, 2023)
One of the main limitations of the cucurbit crops production is the powdery mildew disease, caused by the biotrophic fungus Podosphaera xanthii. An integrated management, using several strategies, is carried to control the disease but the application of fungicides is the most effective one. The problem is that P. xanthii has been classified by the Fungicide Resistance Action Committee (FRAC) as a pathogen with a high risk of resistance developing, in addition of the strong restrictions on the use of phytosanitary products at a European level. For this reason, new phytosanitary tools are necessary to allow a sustainable control of this devastating disease such as the use of the RNA interference (RNAi) technology. In this work, dsRNA targeting a P. xanthii gene, which encodes a protein that appears to be essential for the correct assembly of the fungal cell wall, was evaluated. Preliminary gene silencing results have shown a significant reduction of fungal development on melon plants suggesting that this gene may be a promising target for the control of powdery mildew of cucurbits. This work has been funded by AEI (PID2019-107464RB-C21).
Keywords: Hongos fitopatógenos; Cucurbitáceas - Enfermedades y plagas; Podosphaera xanthii; SIGS; Proteina anclada GPI